Regulation of prostitution in the Netherlands: liberal dream or growing repression? - Post, Che (European journal on criminal policy and research, 2019)
This paper focuses on the regulation of prostitution in the Netherlands from the twentieth century onward. It aims to provide a full description of the Dutch position on prostitution through the interpretation and explanation of current Dutch prostitution policy. This will be achieved by analyzing the legal narratives that substantiate the legal rules provided in both Dutch criminal and administrative law concerning the regulation of prostitution. We analyze the Dutch prostitution legislation of the past, present, and future, using a newly developed analytical framework. Using this framework, we reconstruct the legislator’s attitude towards prostitution using insights from previous theoretical work on prostitution and using models aimed at regulating this phenomenon that range from a total ban to full decriminalization. In our analysis, we also use the legitimating grounds for application of criminal law developed by Feinberg. These grounds are also used in this paper to interpret the administrative intervention in prostitution. This paper reveals a paradox: The idea of a liberal dream goes hand-in-hand with growing repression of freedom in the Dutch prostitution sector.